Angle-independent solar radiation capture by 3D printed lattice structures for efficient photoelectrochemical water splitting - Hegde, Chidanand (2023)
Photoelectrochemical water splitting is one of the sustainable routes to renewable hydrogen production. One of the challenges to deploying photoelectrochemical (PEC) based electrolyzers is the difficulty in the effective capture of solar radiation as the illumination angle changes throughout the day. Herein, we demonstrate a method for the angle-independent capture of solar irradiation by using transparent 3 dimensional (3D) lattice structures as the photoanode in PEC water splitting. The transparent 3D lattice structures were fabricated by 3D printing a silica sol–gel followed by aging and sintering. These transparent 3D lattice structures were coated with a conductive indium tin oxide (ITO) thin film and a Mo-doped BiVO4 photoanode thin film by dip coating. The sheet resistance of the conductive lattice structures can reach as low as 340 Ohms per sq for ∼82% optical transmission. The 3D lattice structures furnished large volumetric current densities of 1.39 mA cm−3 which is about 2.4 times higher than a flat glass substrate (0.58 mA cm−3) at 1.23 V and 1.5 G illumination. Further, the 3D lattice structures showed no significant loss in performance due to a change in the angle of illumination, whereas the performance of the flat glass substrate was significantly affected. This work opens a new paradigm for more effective capture of solar radiation that will increase the solar to energy conversion efficiency.